The Dynamics of Islamic and Malay Acculturation: Customary Continuity and Value Transformation in Historical Perspective - Azzahra, Radhita; Trisnawati, Nadia; Oviyanti, Fitri; Maryamah, Maryamah (FKIP - Universitas Riau, 2025)
This article discusses the dynamics of acculturation between Islam and Malay culture in a historical perspective, highlighting adat continuity and value transformation. Islamic acculturation in the archipelago did not erase local customs, but rather provided a new foundation based on Islamic values, as reflected in the principle of “adat bersendi syarak, syarak bersendi Kitabullah”. The process of Islam was peaceful through trade, proselytization, education and marriage, with a flexible approach to local culture. Value transformation involved replacing animist and dynamist beliefs with the concept of tawhid, which emphasizes the oneness of God. A Malay-Islamic identity was born from this acculturation, reflected in art, literature, music and customs, creating a unique and harmonious cultural expression. This article concludes that the acculturation of Islam and Malay culture has shaped a rich and diverse civilization, where Islamic values are integrated in Malay cultural life.